2017
DOI: 10.3390/s17122768
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Embedded Conjugated Polymer Sensor Arrays for Potential Load Transmission Measurement in Orthopaedic Implants

Abstract: Load transfer through orthopaedic joint implants is poorly understood. The longer-term outcomes of these implants are just starting to be studied, making it imperative to monitor contact loads across the entire joint implant interface to elucidate the force transmission and distribution mechanisms exhibited by these implants in service. This study proposes and demonstrates the design, implementation, and characterization of a 3D-printed smart polymer sensor array using conductive polyaniline (PANI) structures … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The literature, presents several examples of PANI blending with several host matrices such as poly(n-butyl methacrylate) (PBMA) [13], poly(dimethysiloxe) (PMDS) [11], styrene-butadiene-styrene copolymer (SBS) [14,15] or poly(ethylene-vinyl acetate) (PVAc) [16] with promising piezoresistive behaviour for deformation sensors [17]. By contrast, fewer studies have been reported about PANI composites used in the fabrication of flexible temperature sensors [2].…”
Section: Introductionmentioning
confidence: 99%
“…The literature, presents several examples of PANI blending with several host matrices such as poly(n-butyl methacrylate) (PBMA) [13], poly(dimethysiloxe) (PMDS) [11], styrene-butadiene-styrene copolymer (SBS) [14,15] or poly(ethylene-vinyl acetate) (PVAc) [16] with promising piezoresistive behaviour for deformation sensors [17]. By contrast, fewer studies have been reported about PANI composites used in the fabrication of flexible temperature sensors [2].…”
Section: Introductionmentioning
confidence: 99%
“…To analyze loads in orthopedic implants, a three-dimensionally (3D)-printed sensor array (composed of PANI structures embedded in a polymeric parent phase) was developed. , Linear outputs following fractional changes in resistance occurring during incrementally applied loads, were obtained. For the detection of micromotion, eddy current sensors and factors that affect the sensitivity and range of sensors implanted in the tibia beneath the metallic plate were also investigated .…”
Section: Implant Integrating Sensorsmentioning
confidence: 99%
“…In the same work, challenges related to the development of such implants are discussed, highlighting the need for collaboration among stakeholders to realize these novel applications. For in situ measurements of implant performance, Micolini and colleagues 40 demonstrated the use of AM to fabricate a polymer sensor array with conductive polyaniline that can be embedded into implants for in-situ measurement of load transmission. Besides that, AM is also being used as a prototyping tool for testing new research approaches.…”
Section: Applications In Total Joint Arthroplastymentioning
confidence: 99%